2020
DOI: 10.1016/j.stemcr.2020.05.012
|View full text |Cite
|
Sign up to set email alerts
|

VCAM1 Labels a Subpopulation of Neural Stem Cells in the Adult Hippocampus and Contributes to Spatial Memory

Abstract: Summary Active neural stem cells (aNSCs) and quiescent neural stem cells (qNSCs) are two distinct subpopulations found in the adult hippocampal dentate gyrus (DG). However, to date, no cell surface marker has been established to identify and profile qNSCs in the adult hippocampus. Here, we identified expression of vascular cell adhesion molecule 1 (VCAM1) on the cell surface of NSCs, through which we identified a previously unrecognized subpopulation of NSCs in the adult mouse DG. Interestingly, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…We searched the literature for candidate genes/proteins exhibiting dynamic level changes during the transition period in NSCs. Vcam1 is expressed by both embryonic and adult NSCs 46,60 . Interestingly, the Vcam1 protein is widespread in the embryonic germinal zone and the distribution becomes more restricted in the V-SVZ during the first three postnatal weeks as radial glial transition into adult NSCs 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We searched the literature for candidate genes/proteins exhibiting dynamic level changes during the transition period in NSCs. Vcam1 is expressed by both embryonic and adult NSCs 46,60 . Interestingly, the Vcam1 protein is widespread in the embryonic germinal zone and the distribution becomes more restricted in the V-SVZ during the first three postnatal weeks as radial glial transition into adult NSCs 46 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the Vcam1 protein is widespread in the embryonic germinal zone and the distribution becomes more restricted in the V-SVZ during the first three postnatal weeks as radial glial transition into adult NSCs 46 . Importantly, Vcam1 maintains the subpopulation of embryonic NSCs destined to become adult neural stem cells 46 ; NSCs are prematurely depleted in Vcam1 -knockout mice 60 . Furthermore, Vcam1 is necessary for maintaining the V-SVZ structure in adults 61 .…”
Section: Resultsmentioning
confidence: 99%
“…6E ). It was reported that VCAM1 + cells exhibited more stem cell characteristics in neural stem cell populations [ 29 ], which implies that stem cells may express high levels of VCAM1. In fact, a positive correlation between LSC level and VCAM1 expression was observed in the datasets GSE92969 and GSE115549 [ 4 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Double-immunostaining revealed that these Mito-tracker-positive cells coexpress well with nestin ( Figure 3(b) ), suggesting the neural progenitor identity of these cells. There are two populations of progenitors in the hippocampus, active neural stem cells (aNSCs), and quiescent neural stem cells (qNSCs) [ 16 ], which could be roughly identified by morphology and play important roles in the cognitive function of the hippocampus [ 17 ], namely, aNSCs are horizontal and qNSCs are radial [ 16 ]. To explore if exogenous mitochondria regulate the behavior of neural progenitors in the hippocampus, we focused on Wnt/ β -catenin signal transduction, a pivotal signal path, which regulates the balance of qNSCs and aNSCs [ 16 ], via a Wnt signal transduction reporting mice line, TOPGAL mice [ 18 ].…”
Section: Resultsmentioning
confidence: 99%